Influence of smokeless tobacco on periodontal health status in local population of North India: A cross-sectional study - G P Singh; Iram Rizvi; Vivek Gupta; Vivek K Bains (Wolters Kluwer Medknow Publications, 2011)
Background: Limited studies have been published so far, which revealed the association of different types of smokeless tobacco on various periodontal health indicators, including mobility and furcation, on North Indian population. The present study has been undertaken to evaluate the effects of commonly used smokeless tobacco forms on periodontal health in Lucknow, North India. Methods: This cross-sectional study investigated the effect of commonly used smokeless tobacco on periodontal health in local population of Lucknow, for which 2045 individuals were evaluated. Amongst them, 1069 individuals were found to be using some kind of tobacco; amongst the tobacco users, n=122 were smokers, n=657 were only using only smokeless tobacco and n=290 were using both smokeless tobacco as well as tobacco in smoking form. After completing the questionnaire, all the participants underwent clinical examination for the various clinical parameters. Results: The impact of smokeless form of tobacco use was significantly higher on all the periodontal health indicators, viz., plaque index, gingival index, calculus, clinical attachment loss, gingival recession, mobility, furcation, lesion, and probing pocket depth. Both duration and frequency of smokeless tobacco use significantly affected the periodontal health. Conclusion: The periodontal health of the general population in the region required immediate attention as majority of subjects irrespective of their habit status had onset of clinical attachment loss and gingival recession, more so amongst the smokeless tobacco users than smoking form of tobacco as well as than from non-tobacco users.